2021
DOI: 10.1371/journal.pone.0253989
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating extraction methods to study canine urine microbiota

Abstract: The urinary microbiota is the collection of microbes present in urine that may play a role in host health. Studies of urine microbiota have traditionally relied upon culturing methods aimed at identifying pathogens. However, recent culture-free sequencing studies of the urine microbiota have determined that a diverse array of microbes is present in health and disease. To study these microbes and their potential role in diseases like bladder cancer or interstitial cystitis, consistent extraction and detection o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 98 publications
3
24
0
Order By: Relevance
“…Taxonomic profiles in the study urine samples were dominated by members of the Proteobacteria phylum, which is consistent with previous findings in both dogs and cats. 19 , 20 , 60 In contrast, the genera Lactobacillus and Gardnerella commonly dominate urotypes of women. 25 , 61 , 62 These differences might be a result of variations in urine collection method, anatomic or hormonal differences between species, or other biological or environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taxonomic profiles in the study urine samples were dominated by members of the Proteobacteria phylum, which is consistent with previous findings in both dogs and cats. 19 , 20 , 60 In contrast, the genera Lactobacillus and Gardnerella commonly dominate urotypes of women. 25 , 61 , 62 These differences might be a result of variations in urine collection method, anatomic or hormonal differences between species, or other biological or environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 , 18 In fact, a comprehensive analysis of the gut and urogenital microbiomes determined that the urogenital microbiome exhibited more pronounced alterations by urolith status than did the gut microbiome. 9 Microbial communities also recently have been identified in the urine of healthy dogs, 19 , 20 , 21 but the role of these microbes in CaOx formation in dogs is unknown. Discovery of urogenital microbiome features that discriminate dogs with CaOx urolithiasis from healthy dogs could provide insight into disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Illustrating the importance of the extraction step in an analytical process, two very recent studies have also benchmarked DNA extraction kits for the study of human and canine urine microbiota [20,24]. Mrofchak et al identified the BI kit as having the best extraction method for the study of the urine microbiota, whereas the study by Karstens et al reported that the BI and BT kits gave similar performances.…”
Section: Discussionmentioning
confidence: 99%
“…Urine samples were extracted using QIAamp ® BiOstic ® Bacteremia DNA Isolation Kit (Qiagen, Hilden, Germany) as described previously [68]. Fecal samples were extracted using the QIAamp ® PowerFecal ® DNA Kit (Qiagen, Hilden, Germany) following the manufacturer's instructions.…”
Section: Dna Extraction and Quantificationmentioning
confidence: 99%
“…Likewise, negative controls underwent the full extraction, library preparation, and sequencing process. We amplified the V4 region of the 16S rRNA gene using primers 515F and 806R, and PCR and sequencing were performed as described previously (2 x 250bp paired-end reads, on an Illumina Miseq (Lemont, IL, USA)) [68][69][70]. Raw, paired-end sequence reads were processed using QIIME2 v. 2020.11 and DADA2 [71,72].…”
Section: Dna Extraction and Quantificationmentioning
confidence: 99%